2015
DOI: 10.4137/jmecd.s29926
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Students' Perceptions of Educational Environment in the PBL Program of Sharjah Medical College

Abstract: BACKGROUND: Students' perception of their educational environment has a significant impact on their behavior and academic progress. The recent worldwide usage of innovative problem-based learning (PBL) medical programs requires major changes in medical schools and their environments. Therefore, measuring students' perceptions of the complex PBL environment has become a critical necessity as a determinant of students' academic success and as a part of attaining the quality standards of education. Ours being a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 50 publications
5
13
2
2
Order By: Relevance
“…The only significant were item # 2 (table 2, and # 5 table # 3), which deal with adequacy and availability of library resources when students need them program has improve students' skills in communication respectively. This were obvious in the results of (15,21,22,24) The response about help and support for learning according to year, resources to support learning according to year (table 4 and Significant of the study materials and adequacy and availability of library resources, this was in agreements with the results of 16,17,19,21,22,23,24. Those demonstrated that graduated founded the needed material at the library each time they needed.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The only significant were item # 2 (table 2, and # 5 table # 3), which deal with adequacy and availability of library resources when students need them program has improve students' skills in communication respectively. This were obvious in the results of (15,21,22,24) The response about help and support for learning according to year, resources to support learning according to year (table 4 and Significant of the study materials and adequacy and availability of library resources, this was in agreements with the results of 16,17,19,21,22,23,24. Those demonstrated that graduated founded the needed material at the library each time they needed.…”
Section: Discussionsupporting
confidence: 78%
“…The results showed no significant different between gender, which was not agreed with the results founded at Sultan ZainalAbidin Medical College, Malyzia by Rahman et al (20) and at Sharjah Medical College, United Arab of Emirates by Nosair et al (22). This differences could be explained by the sample size.…”
Section: Discussioncontrasting
confidence: 56%
“…Generally the responses about the student support services according to gender, was highly differences between the both gender as shown in (19)(20).About the support services our results showed that, fifth year were satisfied with the support survives in the college campus (table 4). This is in parallel and strongly agreed with the finding of Nosair et al (16). But disagreed with Buhaimed et al (22), those concluded that, they should improve their educational environment in order to advance the quality of the delivered curriculum among their students.Students' perception of their educational environment was positive at both Rabigh and Jeddah campuses of King Abdulaziz University Imran et al (18).…”
Section: Students Experience Survey About the Quality Of Learning At supporting
confidence: 64%
“…First, we computed the descriptive statistics including frequency, mean and standard deviations of the perceptions' scores for individual items, sub-domains and total DREEM. A guide to score interpretation was provided in a similar publication (12).…”
Section: Quantitative Data Analysismentioning
confidence: 99%
“…Although several studies have explored the strengths and weaknesses of EEs around the world (4,6,(8)(9)(10)(11)(12), there is very limited information relevant to the UR. A recent study (13) explored the perception of the EE in the UR, but it was limited to physiotherapy students only.…”
Section: Introductionmentioning
confidence: 99%